Designing a Web-Based Information System for Educational Decision Support: Merancang Sistem Informasi Berbasis Web untuk Pendukung Pengambilan Keputusan Pendidikan - Afidah, Dewi Nur; Astutik, Ika Ratna Indra; Indahyanti, Uce; Azinar, Azmuri Wahyu (Indonesian Journal of Islamic Studies, 2025)
Background: Education in the digital era requires effective and efficient information systems to support data management and decision-making processes. Knowledge Gap: Previous studies focused more on technical development without emphasizing usability and data accuracy aspects in educational contexts. Aims: This study aims to design and develop a web-based information system to facilitate effective educational decision-making. Results: The results show that the proposed system successfully improves data accessibility, simplifies processing, and ensures higher accuracy compared to previous manual methods. Novelty: The novelty lies in the integration of multi-user access and real-time reporting features that enhance system efficiency in the education environment. Implications: The findings contribute to improving information management performance in educational institutions and provide a reference for future system development. Highlights:• Development of a web-based educational decision support system• Integration of real-time access and multi-user features• Increased accuracy and efficiency in educational data management Keywords: Web-based System, Education Technology, Decision Support, Data Management, Usability